Explaining Racial Differences in Ferguson’s Impact on Local Residents’ Trust and Perceived Legitimacy: Policy Implications for Police: - Kochel, Tammy Rinehart (Criminal justice policy review, 2019)
Public support and trust are critical to effective democratic policing, but scholars have suggested police in the United States may be experiencing a legitimacy crisis. High-profile police-involved shootings like those which have happened over the last 2 years can have negative consequences. This study assesses the consequences of the Ferguson, Missouri unrest and police response on local residents’ views. A panel survey of St Louis County, Missouri residents conducted before and after the police shooting of Michael Brown examines the effects on procedural justice and trust, police legitimacy, and willingness to cooperate with police. Results reveal a significantly different effect on African American versus non-Black residents. African Americans’ views significantly declined while non-Black residents’ perceptions were stable. Qualitative data are used to apply the conflict/group position and accumulated experience theories to explain racial disparities and are used as a basis to offer strategies to improve confidence and trust in police.